Aerospace Technology Improves Fermentation Potential of Microorganisms - Chi, Yan; Wang, Xuejiang; Li, Feng; Zhang, Zhikai; Tan, Peiwen (Frontiers in Microbiology, 2022)
It is highly possible to obtain high-quality microbial products in appreciable amounts as aerospace technology is advancing continuously. Genome-wide genetic variation in microorganisms can be triggered by space microgravity and radiation. The mutation rate is high, the mutant range is wide, and the final mutant character is stable. Therefore, space microorganism breeding is growing to be a new, promising area in microbial science and has greatly propelled the development of fermentation technology. Numerous studies have discovered the following improvements of fermentation potential in microorganisms after exposure to space: 1) reduction in fermentation cycle and increase in growth rate; 2) improvement of mixed fermentation species; 3) the increase in the bacterial conjugation efficiency and motility; 4) improvement of the bioactivity of various key enzymes and product quality; 5) enhancement of multiple adverse stress resistance; and 6) improvement of fermentation metabolites, flavor, appearance and stability. Aerospace fermentation technology predominantly contributes to bioprocessing with microgravity environment. Unlike the terrestrial fermentation, aerospace fermentation keeps cells suspended in the fluid medium without the significant shear forces. Space radiation and microgravity have physical, chemical and biological effects on mutant microorganisms by causing the alternation in fluid dynamics, genome, transcriptome, proteome, and metabolome levels.